Gaji Guru Taman Pendidikan Al-Qur’an dalam Perspektif Ekonomi Syari’ah - Tsaniyatul Karimah; Malichatul Istifadah (Maliyah : Jurnal Hukum Bisnis Islam, 2018)
Al-Qur'an Education Park (TPQ) is an educational institution that supports formal education in schools. The teacher as a component in teaching and learning activities has a very important role in determining the success of learning. The role of the TPQ teacher is not only to educate students so that they can read and write the Qur'an properly and correctly, but also so that students can live an Islamic life. The purpose of this journal is to find out more about the meaning of teachers and their role in education, and how Islamic economics views their welfare. This research was conducted through observation and interviews. The data obtained were analyzed using the Islamic economic approach. The results obtained from this study were that TPQ teachers received a monthly salary, the amount of which was adjusted to their respective TPQ. The salary received is still below the UMR standard. However, TPQ teachers are still enthusiastic about teaching because they teach TPQ because of their heart's calling and they simply want to practice their knowledge by ignoring the value of the material they will get. Based on Islamic economics, the TPQ salary is related to the concept of ujrah and ijarah. They are entitled to a salary, and it is better if the salary can be increased again so that it is equal to their profession and so that TPQ education will be of higher quality.